Mobile App Marketing ‘Oluhuta Journey’ as A Promotion and Marketing Tool for Edu-Geotourism in Oluhuta Village - Samiputri Ayu Saridjan; Intan Noviantari Manyoe; Nurul Istiqamah Kadekoh; Dinar Amalia Khansa; Muhammad Asram Tongkodu; Muh. Nur Alfian S. Kasim (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Information and communication technology has become a necessity in all aspects of life, including the tourism sector. The tourism sector needs that in promoting and marketing a tourism destination through various digital-based media to reach more potential tourists in a short time. For this reason, the team of Holistic Program for Village Development and Empowerment of Student Activity Unit of Literacy, in their main program to optimize the potential of the Oluhuta early human site, the coral reef terrace site, as well as the various geo-diversity and bio-diversity wealth found in Oluhuta Village, created an innovation in the form of Android-based mobile app marketing and a Geographic Information System (GIS) called Oluhuta Journey as a marketing and promotion tool for edu-geotourism in Oluhuta Village. The purpose of this article is to explain and describe the process of designing, manufacturing, and training Oluhuta Journey Mobile App Marketing. The result showed the unique features contained in the mobile app marketing are possible to reach and attract both local and foreign tourists to visit Oluhuta Village.